IN VITRO FUNCTIONAL CHARACTERIZATION AND TOXICITY ASSESSMENT OF A RECOMBINANT ACE2-LIKE ENZYME FROM BACILLUS CEREUS SP. AS THERAPY IN SARS-COV-2-INDUCED LUNG INJURY - Arie Anggraeni, Novi
Exogenous ACE2, such as recombinant human ACE2 (rhACE2), can be an alternative therapy for SARS-CoV-2 infection by inhibiting the interaction of the virus with ACE2 and modulating RAS, thereby protecting the lungs from acute lung injury. rhACE2 increases the activity of soluble ACE2, reduces Ang II, and produces Ang (1-7). One alternative to exogenous ACE2 is an ACE2-like enzyme from bacteria, such as the B38-CAP enzyme from Paenibacillus sp. B38. This enzyme is an M32-carboxypeptidase that can convert Ang II to Ang (1-7) but can also inhibit SARS-CoV-2. Previous studies have succeeded in producing recombinant ACE2-like enzyme from Bacillus cereus sp. (rBceCP) but have not confirmed the activity and toxicity of the enzyme. Before the activity test was carried out, the results of the expression of the gene encoding the B. cereus sp. carboxypeptidase. (Bcecp) inserted into the recombinant plasmid and transformed into E. coli BL21(DE3) was confirmed using Western Blotting after being purified with a Ni-NTA column. To determine the mode of action against Ang I, a hydrolysis test was carried out using HPLC and LCMS. The inhibition test was carried out using ELISA-like against the SARS-CoV-2 spike protein. In the final stage, a cytotoxicity test was carried out against Vero E6 cells at a concentration of 0-10 ?M rBceCP using the MTT assay method. This study successfully confirmed the purified rBceCP enzyme (60.3 kDa) by affinity chromatography. The hydrolysis activity of rBceCP against Ang I was detected at a retention of 4.6 minutes with Ang (1-9) products (1,183.6012 m/z) and leucine (132.1024 m/z). rBceCP was also found to be able to inhibit the SARS-CoV-2 spike protein twice as high as the control (44% vs 28%) and was not toxic to cells (58% viability at 10 ?M). These results indicate that rBceCP is an ACE2-like enzyme and can protect lung pathology in COVID-19 patients.